Quantum voting protocol without quantum memory - Xu, Lidong; Wang, Mingqiang (Frontiers in Physics, 2022)
Most of the quantum voting protocols are impractical due to the currently limited quantum storage capabilities. In this article, based on the interference principle of light, we proposed a new quantum voting protocol without quantum memory. In our protocol, the ballot is a sequence of non-orthogonal coherent states, the voting information is encoded by implying different phase shifts on the coherent states, and the vote counting is carried out by performing USD measurement on the coherent states. Particularly, the design of USD measurement on coherent states eliminates the need for quantum storage. Our protocol satisfies the general security requirements of quantum voting protocols and can resist various attacks. In addition, our protocol can be implemented by only linear optics and thus can be experimentally achieved with current technology.